PROBLEMATICS OF HALAL PRODUCT SERVICE DEVELOPMENT (HALAL CENTER) AT BALITAR ISLAMIC UNIVERSITY - susetiyo, weppy; Sulistyo, Anjarwati; Choirunnisa Rizky , Nockita (Metafora: Education, Social Sciences and Humanities Journal, 2024)
This research aims to evaluate and identify the challenges faced by the Halal Center at Balitar Islamic University (UNISBA), Blitar, as well as provide recommendations for improving halal certification services. The research method used is normative law with a statutory and conceptual approach. Data was collected through legal documents, literature and scientific journals, with qualitative analysis to connect the data with legal theory. The research results show that the UNISBA Halal Center faces challenges related to limited resources, public awareness and regulatory bureaucracy. However, the Halal Product Process Companion (PPH) training that was held showed high enthusiasm and an urgent need for assistance in halal certification. Recommendations include simplifying certification procedures, providing subsidies, and increasing awareness about halal standards to support the growth of the halal industry at local and national levels. Keywords : Halal Services, Problems; Halal Products.